2020
DOI: 10.3390/microorganisms8050707
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Gene Expression in Dermacoccus abyssi HZAU 226 under Lysozyme Stress

Abstract: Lysozyme acts as a kind of cationic antimicrobial protein and effectively hydrolyzes bacterial peptidoglycan to have a bactericidal effect, which also plays an important role in protecting eggs from microbial contamination. Dermacoccus abyssi HZAU 226, a Gram-positive bacterium isolated from spoiled eggs, has egg white and lysozyme tolerance, but its survival mechanism is unknown, especially from a transcriptomics point of view. In this study, the high lysozyme tolerance of D. abyssi HZAU 226 was characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…RNA was extracted based on the method described by Zhang et al [22]. The main reagent used is TRIzol (Invitrogen, Carlsbad, CA, USA), which is a new total RNA extraction reagent that can directly extract total RNA from cells or tissues.…”
Section: Extraction and Purification Of Rna From Suspended Aggregates Or L Monocytogenesmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA was extracted based on the method described by Zhang et al [22]. The main reagent used is TRIzol (Invitrogen, Carlsbad, CA, USA), which is a new total RNA extraction reagent that can directly extract total RNA from cells or tissues.…”
Section: Extraction and Purification Of Rna From Suspended Aggregates Or L Monocytogenesmentioning
confidence: 99%
“…RNA-seq library preparations were built based on the manufacturer's manual, and the Ribo-Zero rRNA removal kit (Bacteria, Illumina, San Diego, CA, USA) was applied to the loss of ribosomal RNA. The construction of the RNA-seq library mainly refers to the method of Zhang et al [22]. The basic process includes RNA interruption, doublestranded cDNA synthesis, terminal repair, dA-tailing, splice, fragment sorting, digestion of dUTP-labeled double strand and PCR amplification.…”
Section: Library Construction and Sequencingmentioning
confidence: 99%
“…Expression of sRNA23 was downregulated under iron deprivation medium, which was consistent with the results of RNA-seq. In addition, like many sRNAs, sRNA23 expression was induced by oxidative and lysozyme stress [ 42 , 43 ]. These findings suggest that differential expression of sRNA23 to different environments may be beneficial for bacterial adaptation and pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, RNA-seq is a transcriptome analysis technique commonly used to explore microorganisms’ tolerance mechanism and analyze differentially expressed genes (DEGs) in transcriptomes ( Mo et al 2019 ). Zhang et al (2020) revealed the lysozyme tolerance mechanism of Dermacoccus abyssi through RNA-seq, and their results showed that the tolerance mechanism of the strain is related to the gene expression of glutathione biosynthesis and metabolism, ion transport, energy metabolism pathway, and peptidoglycan synthesis. The metabolic rule of Ethanoligenens harbinense in ethanol-type fermentation of anaerobic acidogenesis at different pH was studied by RNA-seq, and the results showed that low initial pH resulted in down-regulated expression of genes related to cell growth and acidification.…”
Section: Introductionmentioning
confidence: 99%